2021
DOI: 10.3390/diagnostics11071266
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Improve Primary Care Patient Management and Patient Outcomes Using a Drug–Drug Interaction Test: Confirmation of the DECART Simulated Patient Clinical Utility Trial Results

Abstract: Drug–drug interactions (DDIs) are a serious problem in the healthcare system, leading to excess healthcare utilization and costs. We conducted a second prospective randomized, controlled trial to further establish the real-world clinical utility of a novel assay that objectively identifies potentially serious DDIs in real-world patients. Re-recruiting primary care physicians (PCPs) from our first randomized, controlled, simulated-patients study on DDIs, we experimentally introduced a definitive, urine-based ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The limitations of this study include the use of simulated patients; however, other research comparing simulated patient research with real-world patient studies indicates that real-world studies would broadly substantiate this study's findings ( 38 , 39 ). We used a national sample of gastroenterologists and GI surgeons.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The limitations of this study include the use of simulated patients; however, other research comparing simulated patient research with real-world patient studies indicates that real-world studies would broadly substantiate this study's findings ( 38 , 39 ). We used a national sample of gastroenterologists and GI surgeons.…”
Section: Discussionmentioning
confidence: 73%
“…As such, it is possible that unexplained heterogeneity may make selected participants systematically different from the national norm or other groups of physicians. This study did not factor in the variability of the histopathology reports that participants evaluated in making their clinical decisions ( 38 , 39 ). Another limiting factor is variable participant interpretation of the educational materials.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies have shown that the results from simulated patient studies using the validated tool are the same as results from similarly conducted studies in real-world patients. This suggests use of simulated patient studies may accelerate the evaluation of clinical utility [ 36 , 37 ]. Whether these improvements in care due to the CVD-T2D test will translate to real world patients remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that in a selected patient population taking four or more drugs, 78.4% had a moderate to severe DDI [15]. Evidence shows that DDI testing in real-world patients significantly improves the management of polypharmacy, DDIs, and patient outcomes [16].…”
Section: Introductionmentioning
confidence: 99%